2015
DOI: 10.1016/j.ibusrev.2014.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Five star hotels of a Multinational Enterprise in countries of the transitional periphery: A case study in human resources management

Abstract: The paper examines the application of human resource management (HRM) practices by a Multinational Enterprise (MNE) whose operations extend from unexplored post-Soviet countries' transitional periphery economies to advanced economies. By involving hotels of a global luxury US chain in Azerbaijan (Caucasus) and Kyrgyzstan (Central Asia), this in-depth case study focuses on the labour-intensive hospitality industry which, although being relatively neglected by mainstream research, is among the first movers in ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 139 publications
(145 reference statements)
1
19
0
Order By: Relevance
“…Solnet, Kralj and Baum (2013) advocated for more scholarly research on human resources management in the tourism industry; the work observed an alarming dearth of studies in the tourism industry, especially in emerging economies such as Nigeria. However, Zampoukos and Loannides (2015) stated that hospitality sector is the most visible component of the economy of tourism industry; it is labour intensive in nature Serafini and Szamosi (2015), and requires skilled and knowledgeable human power for it to deliver (Kusluvan, Kusluvan, Ilhan and Buyruk, 2010). In Ghosh and Gurunathan (2015) it was found that individual human resource practice is less effective on employees compared with the bundle of human resource management practices such as compensation, growth opportunity amongst others, which are more positively impactful on the employee job outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Solnet, Kralj and Baum (2013) advocated for more scholarly research on human resources management in the tourism industry; the work observed an alarming dearth of studies in the tourism industry, especially in emerging economies such as Nigeria. However, Zampoukos and Loannides (2015) stated that hospitality sector is the most visible component of the economy of tourism industry; it is labour intensive in nature Serafini and Szamosi (2015), and requires skilled and knowledgeable human power for it to deliver (Kusluvan, Kusluvan, Ilhan and Buyruk, 2010). In Ghosh and Gurunathan (2015) it was found that individual human resource practice is less effective on employees compared with the bundle of human resource management practices such as compensation, growth opportunity amongst others, which are more positively impactful on the employee job outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, while case study research can be a source of ground-breaking, novel theoretical insights, its theorising potential is not fully exploited in international business research (Welch, Piekkari, Plakoyiannaki, and Paavilainen-Mäntymäki, 2011). Recent contributions, however, highlight the further consideration of case study research as a useful method to examine various contexts and aspects related to international business (e.g., Serafini and Szamosi, 2015;Vahlne and Jonsson, 2016;Zaefarian, Eng, and Tasavori, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…The first point of discussion regarding why SHRM tactics should not be underestimated by Ghanaian MNEs is because the work is labor-intensive. All work in the hospitality industry is deemed "labor intensive" due to its high degree of people-to-people interaction (Tavitiyaman et al 2012, Serafini and Szamosi 2015, Enz 2009, Kandampully et al 2011. Agbodo-Otinpong (2015) states the "main reasons why the hotel industry attracts certain kinds of employees may be due to the poor reputation for its conditions of service, heavy workloads and long working hours, high stress, low pay rates, few promotion opportunities and poor job security and low morale" (p. 15).…”
Section: The Added Value Of Shrm For Ghanaian Mnesmentioning
confidence: 99%
“…"According to the World Travel & Tourism Council, tourism rates among the world's largest employers… Nonetheless, there is alarming dearth of scholarly research on HRM applied in the tourism industry" (Serafini and Szamosi 2015) The effects of globalization, a broad and abstract concept, can be better conjectured through a close study of the various industries that are associated with the phenomenon. Since the rise of the global economy and international travel correlate on so many levels, it stands to reason that the international tourism and hospitality industries can serve as the industries whose study can reveal more about the much-deliberated trends and impact of globalization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation